Friction reducing agent for hard carbon thin film surface, and structural member

By using the methylpropionate polymer with the backbone and side chain structure as the friction reducing agent on the surface of the hard carbon film, the problem of poor friction reduction effect in the prior art is solved, and a more efficient friction reduction and friction overheating effect is achieved.

JP2025066264APending Publication Date: 2025-04-23MITSUBISHI CHEM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023175724
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-23

AI Technical Summary

Technical Problem

The prior art is not effective enough to reduce the friction of the hard carbon film surface, and in a low viscosity lubricant environment, the friction load on the metal contact surface increases, resulting in insufficient effect of the friction reducing agent.

Method used

A methylpropionate-based polymer with a backbone and side chain polymer structure, specifically including derivatives of methylpropionate and propionate, is used as a friction reducing agent to increase its friction reducing agent on the surface of a hard carbon film through the structural design of the polymer.

Benefits of technology

It significantly improves the friction reduction effect of hard carbon film surface and enhances the performance of friction reducing agent. Especially in low viscosity lubricant environment, it can effectively reduce friction and prevent friction overheating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066264000001
    Figure 2025066264000001
  • Figure 2025066264000002
    Figure 2025066264000002
  • Figure 2025066264000003
    Figure 2025066264000003
Patent Text Reader

Abstract

To provide a friction reducing agent for a hard carbon thin film surface and a structural member which are excellent in friction reducing effect.SOLUTION: A friction reducing agent for use on a component having a hard carbon thin film on a surface thereof comprises a (meth)acrylic graft copolymer (A) having a backbone polymer structure and a side chain polymer structure, the side chain polymer structure including constitutional units derived from alkyl (meth)acrylate (a) having an alkyl group with a carbon number of 11 to 30.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a friction reducing agent for hard carbon thin film surfaces used in engine oils, etc., and a structure Regarding parts. [Background technology]

[0002] Lubricants, such as those used in automobile engines and drivetrains, reduce energy loss due to friction. Various friction reducing agents are blended to reduce friction and to extend the life of the equipment by preventing seizure. In recent years, the viscosity of lubricating oils has been reduced in order to reduce fuel consumption, and the load on the contact surfaces between metals has also increased. The loads are becoming more severe, and the role of friction reducers is becoming more important. As for reducers, oiliness improvers such as long-chain fatty acid esters and fatty acid amides, and phosphate esters are used. antiwear agents such as zinc dithiophosphate, organic sulfur compounds and organic halogen compounds, etc. These include extreme pressure agents, organic molybdenum compounds, and other friction modifiers, but these vary depending on the conditions and environment in which they are used. In some cases, the friction reducing effect may be insufficient using only these additives. To overcome this issue, research is underway to use polymer materials as friction reducers. In addition to the friction reducer, the surface structure of the structural member also plays an important role. Attempts have been made to coat the surface with hard thin-film materials, particularly DLC (Diamond-Like Carbon). Since it exhibits excellent wear resistance, low friction, and chemical stability, it is expected to be used as a low-friction sliding material. Therefore, a friction reducer using a polymer material and a structural member coated with DLC were used. Research is currently being conducted into the combination of these components to reduce friction and prevent seizure. The structural member has a hard carbon thin film formed on the sliding surface, and an amine of an ethylenically unsaturated monomer is applied to the structural member. The friction characteristics are improved by using polymer materials containing silane derivatives as friction reducing agents. Patent Document 2 also discloses that a hard carbon thin film is applied to the sliding surface. The formed structural member contains a nitrogen-based polar group and / or an oxygen-based polar group in the alkyl group. The friction characteristics can be improved by using polyalkyl methacrylate as a friction reducer. It has been disclosed that: [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2014-516097 [Patent Document 2] JP 2006-306938 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the methods described in Patent Documents 1 and 2 are insufficient in reducing friction.

[0005] The object of the present invention is to provide a friction reducing agent for hard carbon thin film surfaces and structural members having excellent friction reducing effects. The purpose is to provide. [Means for solving the problem]

[0006] The present invention has the following aspects. [1] A polymer having a main chain structure and a side chain polymer structure, and an alkyl group having 11 to 30 carbon atoms. The side chain polymer structure contains a structural unit derived from alkyl (meth)acrylate (a). (h) A friction reducer for hard carbon thin film surfaces, comprising an acrylic graft copolymer (A). [2] The main chain polymer structure is an alkyl(meth)acrylate having an alkyl group of 1 to 10 carbon atoms. A friction reducer for hard carbon thin film surfaces [1], which contains structural units derived from rate (b). [3] The (meth)acrylic graft copolymer (A) is further represented by the following general formula (1): For hard carbon thin film surfaces of [1], which contains a structural unit derived from (meth)acrylate (c). Friction reducer. [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 contains a hydrogen atom or a polar group represents an organic group that [4] The polar group of the (meth)acrylate (c) is a hydroxyl group or a carboxyl group. [3] A friction reducer for hard carbon thin film surfaces. [5] The (meth)acrylic graft copolymer (A) is a vinyl radical polymerizable monomer. The hard polymer [1] contains a structural unit derived from the monomer (m1) and a structural unit derived from the macromonomer (M). Friction reducing agent for carbon thin film surfaces. [6] The hard carbon thin film according to [5], wherein the macromonomer (M) has a structure represented by the following formula (2): Friction reducer for film surfaces. [ka] (In the formula, X 1 ~X n-1 each independently represents a hydrogen atom, a methyl group, or CH2OH. S, Y 1 ~Y n are each independently a monomer constitutional unit of the macromonomer (M), X bonded to the vinyl group of a certain vinyl radical polymerizable monomer (m2) 1 ~X n-1 Other than represents a substituent. Z represents a terminal group, and n represents an integer of 2 to 10,000. [7] A lubricating oil composition comprising the friction reducer for hard carbon thin film surfaces according to any one of [1] to [6]. . [8] A polymer having a main chain structure and a side chain polymer structure, wherein the alkyl group has 11 to 30 carbon atoms. The side chain polymer structure contains a structural unit derived from alkyl (meth)acrylate (a). (a) a friction reducer including an acrylic graft copolymer (A), and a plurality of parts, A structural member, at least one of the plurality of components having a hard carbon thin film on a surface thereof. [9] The structural member according to [8], wherein the hard carbon thin film is a DLC thin film.

[10] The main chain polymer structure is an alkyl(meth)acrylate having an alkyl group of 1 to 10 carbon atoms. A structural component [8] containing building blocks derived from Relate(b).

[11] The (meth)acrylic graft copolymer (A) further comprises a compound represented by the following general formula (1): A structural member according to [8], comprising a constitutional unit derived from the (meth)acrylate (c) shown. [ka] (In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 contains a hydrogen atom or a polar group represents an organic group that

[12] The polar group of the (meth)acrylate (c) is a hydroxyl group or a carboxyl group.

[11] is a structural component.

[13] The (meth)acrylic graft copolymer (A) is a vinyl radical polymerizable monomer. [8], which contains a monomer (m1)-derived building block and a macromonomer (M)-derived building block. Structural components.

[14] The macromonomer (M) has a structure represented by the following formula (2), Material. [ka] (In the formula, X 1 ~X n-1each independently represents a hydrogen atom, a methyl group, or CH2OH. S, Y 1 ~Y n are each independently a monomer constitutional unit of the macromonomer (M), X bonded to the vinyl group of a certain vinyl radical polymerizable monomer (m2) 1 ~X n-1 Other than represents a substituent. Z represents a terminal group, and n represents an integer of 2 to 10,000. Effect of the Invention

[0007] According to the friction reducing agent for hard carbon thin film surfaces of the present invention, a friction reducing agent having a high friction reducing effect is obtained. The adhesive and structural members can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described in detail below. The following embodiments are merely for the purpose of explaining the present invention. This is merely an example and is not intended to limit the invention to this embodiment. It is possible to implement the present invention in various ways without departing from the spirit of the present invention.

[0009] In the present invention, "(meth)acrylic" refers to the total of "acrylic" and "methacrylic". "(Meth)acrylate" is a general term for "acrylate" and "methacrylate." "(Meth)acryloyl group" refers to both "acryloyl group" and "methacryloyl group". It is a general term and is represented by CH2=C(R)-C(=O)- (R is a hydrogen atom or a methyl group). A "macromonomer" is a monomer having a radical polymerizable group or an addition-reactive functional group. "Vinyl radical polymerizable monomer" means an ethylenediamine that is not a macromonomer. It means a monomer having an ethylenically unsaturated bond.

[0010] The friction reducing agent for hard carbon thin film surfaces of the present invention is a (meth)acrylic graft copolymer (A ). The (meth)acrylic graft copolymer (A) is such that at least a part of the constitutional units is (meth)acrylic. (Meth)acrylic copolymer means a copolymer having structural units derived from acrylic monomers. The polymer is made of constituent units derived from monomers other than (meth)acrylic monomers (such as styrene). It may further include a position.

[0011] The (meth)acrylic graft copolymer (A) has a main chain polymer structure and The polymer structure is made up of a side chain polymer structure (branch polymer structure) that is chemically bonded to a trunk polymer structure. In this specification, a graft copolymer is a copolymer having a main chain polymer structure. A polymer has one or more blocks connected as side chain polymer structures to the main chain. The structures of the polymer and the side chain polymer may be different or the same. The method for producing the polymer is not particularly limited, but may be a polymer having a radical polymerizable double bond at the end. After the chromomonomer is produced as a side chain polymer structure, the monomer that will become the building block of the main chain polymer is A method of radical polymerization with a main chain polymer having a reactive site and a macromer having a reactive site A method in which monomers are prepared in advance and then reacted; a method in which hydrogen is drawn after the main chain polymer is prepared. Using an initiator with the ability to separate, radicals are generated on the main chain polymer, and the side chain polymer is A method of producing a side chain polymer structure by reacting monomers that serve as structural units can be mentioned.

[0012] The (meth)acrylic graft copolymer (A) is a graft copolymer having an alkyl group having 11 to 30 carbon atoms. A constituent unit derived from alkyl (meth)acrylate (a) (hereinafter also referred to as "component (a)"). It is a graft copolymer that contains a side chain polymer structure.

[0013] Examples of the component (a) include n-undecyl (meth)acrylate and i-undecyl (meth)acrylate. Sil(meth)acrylate, n-dodecyl(meth)acrylate, i-dodecyl(meth)acrylate Acrylate, n-tridecyl (meth)acrylate, i-tridecyl (meth)acrylate acrylate, n-tetradecyl (meth)acrylate, i-tetradecyl (meth)acrylate , n-cetyl (meth)acrylate, i-cetyl (meth)acrylate, n-stearyl (Meth)acrylate, i-Stearyl (Meth)acrylate, n-Octadecyl (Meth)acrylate ) acrylate, i-octadecyl (meth)acrylate, n-behenyl (meth)acrylate acrylate, i-behenyl (meth)acrylate, etc. These are used in combination of two or more kinds. This is also fine.

[0014] Charcoal is used as component (a) because of its excellent solubility in base oil and friction reducing effect. A linear or branched alkyl (meth)acrylate having a prime number of 11 to 20 is preferred. Linear or branched alkyl methacrylate having 11 to 20 carbon atoms is more preferred. Linear or branched alkyl methacrylates having 11 to 18 carbon atoms are more preferred. Linear or branched alkyl methacrylates having 12 to 14 carbon atoms are particularly preferred. .

[0015] In addition, the solubility in base oil and the friction reducing performance can be improved, and the lubricating oil composition Since fuel economy can be improved by lowering the viscosity of the component (a), is preferably 30% by mass or more, more preferably 50% by mass or more, based on the total mass of the side chain polymer structure. It is preferable that the content is 80 mass % or more, and more preferable that the content is 80 mass % or more.

[0016] In addition, the solubility in base oil and the friction reducing performance can be improved, and the lubricating oil composition Since fuel economy can be improved by lowering the viscosity of the component (a), is 20% by mass or more and 95% by mass or more based on the total mass of the (meth)acrylic graft copolymer (A). % or less, more preferably 40% by mass or more and 90% by mass or less, and still more preferably 50% by mass or more and 80% by mass or less. % by mass or less is more preferable. The (meth)acrylic graft copolymer (A) has good solubility in base oil. Therefore, the (meth)acrylic graft copolymer (A) has the following constitutional units: It is preferable that the main chain polymer structure also contains a structural unit derived from the component (a).

[0017] The friction reduction performance can be improved, and the fuel economy can be improved by lowering the viscosity of the lubricating oil composition. Therefore, the (meth)acrylic graft copolymer (A) further contains, as a structural unit, (b) an alkyl (meth)acrylate having an alkyl group with 1 to 10 carbon atoms (hereinafter referred to as "component b"); It is preferable that the main chain contains Examples of the component (b) include methyl (meth)acrylate, ethyl (meth)acrylate, and the like. acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n- Pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate (Meth)acrylates having a straight-chain alkyl group such as i-propyl (meth)acrylate; acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, i-nonyl Decyl (meth)acrylate, n-decyl (meth)acrylate, i-decyl (meth)acrylate acrylate, 2-ethylhexyl (meth)acrylate, etc. (meth)acrylate; cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate acrylate, dicyclopentanyl (meth)acrylate, isobornyl (meth)acrylate 4-t-butylcyclohexyl (meth)acrylate and other cyclic alkyl groups (Meth)acrylates are also included. These may be used in combination of two or more kinds.

[0018] Among the components (b), alkylene having 1 to 4 carbon atoms is preferred because of its excellent friction reducing effect. n is an alkyl acrylate, more preferably an alkyl acrylate having 2 to 4 carbon atoms; -butyl acrylate is more preferred.

[0019] It is possible to improve the friction reduction performance and improve fuel economy by reducing the viscosity of the lubricating oil composition. Therefore, the content of the structural units derived from component (b) is based on the total mass of the main chain polymer structure. It is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. It is preferably 80% by mass or more, particularly preferably 90% by mass or more, and most preferably 90% by mass or more. In addition, the solubility in base oil and the friction reducing performance can be improved, and the lubricating oil composition can be made low-temperature. Since the fuel saving property can be improved by increasing the viscosity, the (meth)acrylic graft copolymer The content of the structural unit derived from the component (b) is 5% by mass or more and 9% by mass or less based on the total mass of the body (A). 5% by mass or less is preferable, 20% by mass or more and 90% by mass or less is more preferable, and 40% by mass or less is more preferable. It is more preferably from 50% to 70% by mass, and particularly preferably from 50% to 70% by mass.

[0020] The friction reduction performance can be improved, and the fuel economy can be improved by lowering the viscosity of the lubricating oil composition. Therefore, the (meth)acrylic graft copolymer (A) further contains, as a structural unit, (c) (hereinafter referred to as "component (c)") represented by the following general formula (1): It is preferable to contain a polar group-containing (meth)acrylate (c). .

[0021] [ka]

[0022] (In the formula, R 1 is a hydrogen atom or a methyl group, and R 2 contains a hydrogen atom or a polar group represents an organic group that Examples of the polar group include a hydroxyl group, a carboxyl group, a heterocyclic structure (e.g., a ring having 2 to 4 carbon atoms), and aliphatic heterocycles having 4 to 6 carbon atoms, aromatic heterocycles having 4 to 10 carbon atoms, alkoxysilyl groups, 9 trialkoxysilyl group, phosphate group, amino group, primary amino group having 1 to 6 carbon atoms, and and secondary amino groups having 2 to 6 carbon atoms. -Hydroxyethyl (meth)acrylate, 2-Hydroxypropyl (meth)acrylate , 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate acrylate, 6-hydroxyhexyl (meth)acrylate, glycerin mono (meth) acrylate acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol (Meth)acrylates having a hydroxyl group, such as mono(meth)acrylates; (meth)acrylic Acid, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyl maleate 2-(meth)acryloyloxyethyl phthalate, hexahydrophthalic acid (Meth)acryloyloxyethyl ester or other (meth)acryloyloxyethyl esters containing a carboxy group. tetrahydrofurfuryl (meth)acrylate, glycidyl (meth)acrylate (Meth)acrylates having a heterocyclic structure such as methoxyethyl (meth)acrylates, acrylate, ethoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, etc. Alkoxy (meth)acrylate; 3-(meth)acryloxypropyltrimethoxysilane , 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloyl Dimethylaminoethyl (meth)acrylate, Diethyl aminoethyl (meth)acrylate, (meth)acrylamide, etc. The polar group-containing (meth)acrylate (c) may be used in combination of two or more of these. (Meth)acrylates having an acid group or a carboxy group are preferred, and (meth)acrylates having a hydroxyl group or a carboxyl group are preferred. More preferred are acrylates having a carboxy group, and particularly preferred are acrylates having a carboxy group. The total number of carbon atoms in the polar group-containing (meth)acrylate (c) is preferably 3 to 150, and more preferably 3. The range is more preferably 1 to 50, further preferably 3 to 15, and particularly preferably 3 to 10.

[0023] It has good solubility in base oils and good friction reducing properties, and can reduce the viscosity of lubricating oil compositions. Since fuel saving can be improved by the (meth)acrylic graft copolymer (A The content of the structural unit derived from the component (c) is 0.01% by mass or more relative to the total mass of the component (c). 0% by mass or less is preferable, 0.05% by mass or more and 15% by mass or less is more preferable, and 0.1% by mass or less is more preferable. It is more preferable that the content is from 0.5% by mass to 5% by mass, and particularly preferably from 0.5% by mass to 5% by mass. stomach.

[0024] Since the friction reducing performance can be improved, the structural units derived from the components (a) to (c) The total amount is 70% by mass based on the total mass of the (meth)acrylic graft copolymer (A). Preferably, the content is 80% by mass or more, more preferably 90% by mass or more. It is more preferable that the total amount of the structural units derived from the components (a) to (c) is the above ( The amount does not exceed 100% by mass based on the total mass of the meth)acrylic graft copolymer (A).

[0025] The (meth)acrylic graft copolymer (A) is a copolymer of the (meth)acrylic graft copolymer (A) and the (meth)acrylic graft copolymer (A). The compound derived from another radical polymerizable vinyl compound (d) (hereinafter also referred to as "component (d)") It may contain structural units. Examples of the component (d) include styrene, α-methylstyrene, and pt-butylstyrene. (Meth)acrylates other than vinyl toluene, vinyl acetate and components (a) to (c) Other (meth)acrylates include phenyl (meth)acrylate. , benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy Diethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate ) acrylate, nonylphenoxy polyethylene glycol (meth) acrylate, phen Noxylpolypropylene glycol (meth)acrylate, phenylphenyl (meth)acrylate acrylate, phenylphenoxyethyl (meth)acrylate, phenoxybenzyl (meth)acrylate ) acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate (Meth)acrylates having an aromatic ring structure, such as (1-naphthyl)methyl (meth)acrylate, acrylate; trifluoroethyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate ) acrylate, etc. These may be used in combination of two or more kinds. The (meth)acrylic graft copolymer (A) contains, as a structural unit, the (c), (d ) component in either the main chain polymer structure or the side chain polymer structure. good.

[0026] The (meth)acrylic graft copolymer (A) is a vinyl radical polymerizable monomer ( m1) (hereinafter also referred to as "component (m1)") derived structural unit, and macromonomer (M (hereinafter, also referred to as "component (M)"). , containing a constituent unit derived from a monomer (m2) having a vinyl radical polymerizable group

[0027] The (m1) component may be, for example, styrene, vinyl acetate, or a (meth)acrylate compound. Examples of the (meth)acrylate compound include methyl (meth)acrylate. ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-Decil(meth)acrylate, n-Decyl(meth)acrylate, n-Undecyl(meth)acrylate Acrylate, n-dodecyl (meth)acrylate, n-tridecyl (meth)acrylate , n-tetradecyl (meth)acrylate, n-cetyl (meth)acrylate, n-stearate Linear alkyl acrylates such as tearyl (meth)acrylate and n-behenyl (meth)acrylate (Meth)acrylates having an isopropyl group; i-propyl (meth)acrylate, i-butyl ( (meth)acrylate, t-butyl (meth)acrylate, s-butyl (meth)acrylate , isoamyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, i- Nonyl (meth)acrylate, i-Decyl (meth)acrylate, 3-i-Propylheptan-2-yl undecyl (meth)acrylate, i-undecyl (meth)acrylate, 2-t-butylheptyl i-Dodecyl (meth)acrylate, i-Tridecyl (meth)acrylate ) acrylate, i-tetradecyl (meth)acrylate, i-behenyl (meth)acrylate (Meth)acrylates having branched alkyl groups; cyclopentyl (meth)acrylates; Acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate Dicyclopentenyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate Acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate (Meth)acrylates having cyclic alkyl groups such as 2-hydroxyethyl (meth)acrylates; ) acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (Meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl Xyl (meth)acrylate, Glycerin mono (meth)acrylate, Ethylene glycol hydroxypropyl acrylate, propylene glycol mono(meth)acrylate, etc. (Meth)acrylates having a group; (meth)acrylic acid, succinic acid 2-(meth)acryloyl 2-(meth)acryloyloxyethyl, maleic acid 2-(meth)acryloyloxyethyl, phthalic acid 2-( Meth)acryloyloxyethyl, hexahydrophthalic acid 2-(meth)acryloyloxyethyl (Meth)acrylates containing carboxy groups such as diethyl; phenyl (meth)acrylates acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxyethyl (meth)acrylate Diethylene glycol (meth)acrylate, phenoxypolyethylene glycol ( meth)acrylate, nonylphenoxy polyethylene glycol (meth)acrylate, Phenoxy Polypropylene Glycol (Meth) Acrylate, Phenyl Phenyl (Meth) Acrylate, Phenylphenoxyethyl (meth)acrylate, Phenoxybenzyl ( (meth)acrylate, phenylbenzyl (meth)acrylate, naphthyl (meth)acrylate (Meth)acrylate and (1-naphthyl)methyl(meth)acrylate having an aromatic ring structure Acrylates; Tetrahydrofurfuryl (meth)acrylate, Glycidyl (meth)acrylate (Meth)acrylates and (meth)acrylates having a heterocyclic structure such as (meth)acryloylmorpholine. acrylate; methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate , butoxyethyl (meth)acrylate and other alkoxy (meth)acrylates; allyl ( (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyl o 3-(Meth)acryloxyethyl (meth)acrylate, 3-(meth)acryloxypropyltrimethoxysilane , 3-(meth)acryloxypropyltriethoxysilane, 2-(meth)acryloyl Oxyethyl acid phosphate, trifluoroethyl (meth)acrylate, heptadeca Fluorodecyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, Examples thereof include diethylaminoethyl (meth)acrylate and (meth)acrylamide. These may be used in combination of two or more kinds.

[0028] In order to enhance the friction reducing effect, the component (m1) is preferably made of the components (b) and (c). It is preferred that the copolymer contains 1,2-dichlorophenyl ether. The (M) component is a monomer (m2) having a vinyl radical polymerizable group (hereinafter, referred to as "(m 2) component.) and has a radical polymerizable group at the end. It is a compound containing the component (a) as the component (m2). ) component includes the compounds exemplified above as component (m1).

[0029] The ability to increase the solubility of the (meth)acrylic graft copolymer (A) in the base oil and (M) component contains 50% by mass or more of structural units derived from the (a) component. It is preferable that the content is 60% by mass or more, and more preferable that the content is 70% by mass or more. It is more preferable that the content of the component (M) is 80 mass % or more, and particularly preferable that the content of the component (M) is 80 mass % or more. The structural unit derived from the component (a) may be 100% by mass, or 10 It is preferably less than 0 mass %.

[0030] Furthermore, from the viewpoint of radical polymerization, the component (M) has a structure represented by the following formula (2): preferable.

[0031] [ka]

[0032] (In the formula, X 1 ~X n-1 each independently represents a hydrogen atom, a methyl group, or CH2OH. S, Y 1 ~Y neach independently represents a vinyl group of the monomer structural unit (m2) X binds to 1 ~X n-1 Z represents a terminal group, and n is 2 to 10,000. represents an integer.)

[0033] X 1 ~X n-1 and Y 1 ~Y n are each independently bonded to the vinyl group of component (m2) Y is a substituent. 1 ~Y n For example, OR 1 , halogen atom, COR 2 , COOR 3 , C.N., C.O.N. 4 R 5 , N.H.C.O.R. 6 , or R 7 R 1 ~R 7 are independent shows a hydrogen atom, an alkyl group, an aryl group, a heteroaryl group, etc.

[0034] The terminal group Z is a hydrogen atom, like the terminal group of a polymer obtained by known radical polymerization. and groups derived from radical polymerization initiators.

[0035] In addition, the solubility of the (meth)acrylic graft copolymer (A) in the base oil can be increased. (Meth)acrylic graft copolymers are preferred because they can be used in a wide range of applications and can have a high friction reducing effect. The content of the structural units derived from the component (M) is 1 to 95% by mass relative to the total mass of the component (A). Preferably, the content is 5 to 70% by mass, more preferably 20 to 50% by mass, and further preferably 25 to 70% by mass. 40% by weight is particularly preferred.

[0036] The solubility in base oil and friction reducing performance can be improved, and the lubricating oil composition has a low viscosity. Since fuel economy can be improved by polymerization, the gel permeation chromium of the macromonomer (M) is The mass average molecular weight (Mw) measured by chromatography is preferably 2,000 to 100,000. It is preferably 3,000 to 80,000, more preferably 4,000 to 50,000, and more preferably 5 000 to 30,000 is particularly preferred.

[0037] The solubility in base oil and friction reducing performance can be improved, and the lubricating oil composition has a low viscosity. Since fuel economy can be improved by polymerization, the gel permeation chromium of the macromonomer (M) is The number average molecular weight (Mn) measured by gel permeation chromatography (GPC) is preferably 500 to 30,000. Preferably, it is 3,000 to 20,000, more preferably, it is 5,000 to 16,000. , 8,000 to 12,000 is particularly preferable.

[0038] The solubility in base oil and friction reducing performance can be improved, and the lubricating oil composition has a low viscosity. Since fuel economy can be improved by polymerization, the gel permeation chromium of the macromonomer (M) is The molecular weight distribution (Mw / Mn) measured by chromatography is preferably 1.0 to 5.0, and more preferably 1 A range of 0.3 to 3.0 is more preferable, and a range of 1.5 to 2.5 is even more preferable.

[0039] The component (M) may be one produced by a known method or a commercially available product. The component (M) can be produced, for example, by a method using a cobalt chain transfer agent. method (U.S. Pat. No. 4,680,352), α-substituted unsaturated styrene such as α-bromomethylstyrene, A method of using a compound as a chain transfer agent (International Publication No. WO 88 / 04304), a method of chemically modifying a polymerizable group A method of selectively bonding (JP Patent Publication 60-133007 and U.S. Patent No. 5,147,952) and a method based on thermal decomposition (JP Patent Publication No. 11-240854).

[0040] The number of manufacturing steps is small and a catalyst with a high chain transfer constant is used, so it is advantageous to use a cobalt chain transfer agent. The cobalt chain transfer agent has a high chain transfer constant, so it is preferable to add a small amount of the agent. By adding the tert-butyl ether, it is possible to obtain a macromonomer having a controlled molecular weight.

[0041] As the cobalt chain transfer agent, a known cobalt complex can be used. The amount of the agent is 0.00001 to 0.1 parts by mass per 100 parts by mass of the (m2) component. is preferable, and 0.00005 to 0.05 parts by mass is more preferable, and 0.0001 It is particularly preferably up to 0.02 parts by mass.

[0042] The (meth)acrylic graft copolymer contained in the friction reducing agent for hard carbon thin film surfaces of the present invention The amount of the body (A) is preferably 100% by weight, since it is possible to improve the friction reducing performance of the hard carbon thin film surface friction material. The amount is preferably 70% by mass or more, more preferably 80% by mass or more, based on 100% by mass of the reducing agent. , more preferably 90% by mass or more, and most preferably 95% by mass or more.

[0043] The (meth)acrylic graft copolymer contained in the friction reducing agent for hard carbon thin film surfaces of the present invention is The mass average molecular weight (Mw) of the polymer (A) measured by GPC was determined based on the solubility in base oil and The lubricating oil composition has good friction reducing performance and a low viscosity, which improves fuel economy. If possible, 5000 to 1,000,000 is preferable, and 10,000 to 5,000 is preferable. It is more preferable that the number of the sieving agents is 15,000 or more and 200,000 or less. It is particularly preferable that the molecular weight is 20,000 or more and 200,000 or less.

[0044] The (meth)acrylic copolymer A contained in the friction reducing agent for hard carbon thin film surfaces of the present invention The number average molecular weight (Mn) of the base copolymer measured by gel permeation chromatography (GPC) was The solubility in oil and the friction reducing performance can be improved, and the viscosity of the lubricating oil composition can be reduced. Since this can improve fuel economy, it is preferable that the molecular weight is 3,000 or more and 100,000 or less, and 5,000 or less. More preferably, the number is 10,000 or more and 30,000 or less. It is more preferable that:

[0045] The (meth)acrylic copolymer A contained in the friction reducing agent for hard carbon thin film surfaces of the present invention The molecular weight distribution (Mw / Mn) of the base polymer measured by gel permeation chromatography (GPC) was It has good solubility in oil and good friction reducing performance, and can be used to lower the viscosity of lubricating oil compositions. Therefore, since fuel economy can be improved, the ratio is preferably 1.0 or more and 25 or less, and more preferably 1.5 or more and 15 or less. It is more preferable that the ratio is 2.5 or more and 8.0 or less, and further more preferable that the ratio is 2.5 or more and 8.0 or less.

[0046] An example of the method for producing the friction reducing agent for hard carbon thin film surfaces of the present invention will be described below. The friction reducing agent for hard carbon thin film surfaces of the present invention is a compound in which the alkyl(meth) The acrylate components (a) to (c) and the other radical polymerizable vinyl compound (d) The polymer is produced by polymerizing a monomer mixture containing a macromonomer (M) component by a known method. can. The base oil is not particularly limited, but may be YUBA manufactured by SK Lubricants Co., Ltd. API Group III base oil such as SE3, YUB manufactured by SK Lubricants Base oils that meet API Group III plus standards such as ASE4, polyalphaolefins Examples of base oils include API Group IV base oils such as propylene glycol.

[0047] The polymerization may be carried out under known conditions. Since the effect of suppressing heat generation during polymerization is particularly excellent, It is preferred to use α-methylstyrene dimer as the transport agent.

[0048] The friction reducer containing the (meth)acrylic graft copolymer (A) of the present invention is useful for automobiles and ships. Engine oil, drive oil (gear oil) used in mobility of ships, industrial machinery, robots, etc. It can be used as a friction reducer added to lubricants such as oils, transmission oils, hydraulic oils, and metal processing oils. The (meth)acrylic graft copolymer (A) of the present invention is adsorbed on the surface of the sliding part to form a thin film. By forming this, direct contact between the sliding surfaces is suppressed, thereby reducing friction. The base oils for the engine oil, gear oil, hydraulic oil, etc. are made from crude oil. Examples of such oils include mineral-based base oils and chemically synthesized synthetic oils. API Group III base oils such as YUBASE3 manufactured by SK Lubricants API Group III plus base oils such as YUBASE4 manufactured by our company, polyalcohols, etc. Examples of base oils include API Group IV base oils such as olefins.

[0049] The lubricating oil composition of the present invention comprises a base oil containing the friction reducer for hard carbon thin film surfaces of the present invention. The lubricating oil composition of the present invention is a combination of the friction reducing agent for hard carbon thin film surfaces of the present invention. In addition, other additives may be contained. Other additives include antioxidants, viscosity index improvers, etc. Superplasticizer, pour point depressant, detergent / dispersant, corrosion inhibitor, rust inhibitor, defoamer, emulsifier, antifungal agent , demulsifiers, etc. Also, examples of friction reducers other than those of the present invention include long-chain fatty acid esters. and fatty acid amides and other oiliness improvers, and anti-wear agents such as phosphate esters and zinc dithiophosphates. extreme pressure agents such as organic sulfur compounds and organic halogen compounds, friction agents such as organic molybdenum compounds It may contain regulators and the like. The lubricating oil composition of the present invention may be a grease containing a thickener. Examples of thickening agents include soap-based agents (lithium soap, calcium soap, sodium soap, etc.). soap, aluminum soap, etc.), inorganic (bentonite, silica gel, etc.), organic (Polyurea, polyurethane, etc.)

[0050] The content of the friction reducing agent for hard carbon thin film surfaces of the present invention contained in the lubricating oil composition is When the total mass of the oil composition is taken as 100 mass%, the content is preferably 0.01 to 30 mass%, and more preferably 0.0 The content is more preferably 5 to 25 mass %, and further preferably 0.1 to 20 mass %. By setting the content of the friction reducer for the film surface to 0.01 mass % or more, the friction of the lubricating oil composition can be reduced. The effect is improved, and by making the content 30 mass % or less, the kinetic viscosity of the lubricating oil composition at low temperatures is reduced. and improves fuel economy.

[0051] The structural member of the present invention comprises a (meth)acrylic graft copolymer (A) and a plurality of parts. The structural member of the present invention includes a hard carbon thin film formed on the surface of at least one of the components. Representative parts include camshafts, piston rings, lifters, valves, gearboxes, fuel The present invention can be used for mechanical structural members such as pumps and bearings. As a result, it is used in automobiles, construction machinery, ships, marine structures, dams and water gate facilities, hydroelectric power generation equipment, wind power generation equipment, etc. Examples of such equipment include electrical equipment, food processing equipment, beverage manufacturing equipment, pharmaceutical manufacturing equipment and medical devices.

[0052] As the hard carbon thin film, DLC (diamond-like carbon) thin film can be used. Cut. DLC thin films are amorphous materials that are mainly composed of carbon atoms, and the bond form of the carbon atoms As a diamond structure (sp 3 bond) and graphite structure (sp 2 Combined) In the DLC thin film of the present invention, carbon (sp 3 The proportion of total The amount of the carbon is preferably 20 mol % or more and 90 mol % or less, and more preferably 30 mol % or more and 80 mol % or less. Below is more preferable.

[0053] The DLC thin film is classified according to the constituent elements, and is classified as aC (amorphous), which consists only of carbon. Amorphous carbon, aC:H (hydrogenated amorphous carbon), and titanium and molybdenum. Some metal atoms such as benzene and tungsten, or some nonmetal atoms such as silicon, nitrogen, and fluorine In the present invention, in terms of exerting a significant friction reducing effect, It is preferable to use aC-based material. Among aC-based materials, diamond structure exists. DLC thin films classified as ta-C, which has a high carbon content, are more preferred. The DLC thin film is formed by physical vapor deposition (PVD) or chemical vapor deposition using plasma. It is synthesized by methods such as phase deposition (plasma enhanced chemical vapor deposition, PECVD). The thickness, surface roughness, resistivity, hydrogen content, etc. of DLC thin films are affected by various process parameters, e.g. This can be adapted within wide limits, for example by varying the treatment time.

[0054] The surface roughness of the DLC thin film of the present invention is 0.1 μm or less in terms of arithmetic mean roughness Ra. In other words, if Ra exceeds 0.1 μm, there will be localized scatter. This can result in the formation of fogging and a significant increase in the coefficient of friction. Furthermore, the surface hardness of the DLC thin film is sufficient to ensure the durability of the DLC thin film. When combined with a friction reducer, it has good friction properties and is therefore 1,000HV to 7,000HV is preferable, 2,000HV to 6,800HV It is more preferable that the voltage is 3,000HV or more and 6,500HV or less. It is more preferable that the thickness of the DLC thin film is such that the wear resistance of the DLC thin film can be made sufficient. In order to prevent peeling, the thickness is preferably 0.3 μm or more and 10 μm or less, and more preferably 0.4 μm or more and 1 μm or less. It is more preferable that the thickness is 0.5 μm or less and further preferably 0.7 μm or less.

[0055] The hydrogen content of the DLC thin film is such that good friction properties are obtained when combined with a friction reducer. Therefore, it is preferable that the content is 75 atomic % or less, and more preferably 50 atomic % or less. It is preferably 10 atomic % or less, more preferably 1 atomic % or less. preferable.

[0056] The structural member of the present invention includes a plurality of components, at least one of the plurality of components having a surface The hard carbon thin film is formed on the surface of the parts. For the material, steel, aluminum alloy, aluminum oxide, etc. can be used.

[0057] In the structural member of the present invention, the material of the part on which the hard carbon thin film is not formed is a cast iron. Iron, carburized steel, tempered carbon steel, etc. can be used. Therefore, the surface roughness of the above parts must be 0.1 μm or less in terms of sliding stability. This is preferable.

[0058] A base oil solution containing 2% by mass of (meth)acrylic copolymer was prepared and SRV5 Testing machine (Optimol Instruments Pruftechnik GmbH The disk is coated with a hard carbon thin film material using SUJ2 (high carbon chromium bearing steel) The coefficient of friction measured at 40°C using a ball made of steel is preferably 0.145 or less. It is preferably 0.140 or less, and more preferably 0.138 or less. EXAMPLES

[0059] The present invention will be described in more detail below with reference to examples and comparative examples. In Tables 1 and 2, the content of the structural units derived from each monomer is The content of each structural unit is expressed in mass % based on the total mass of the monomers used in the polymerization reaction. The evaluation was performed by the following method.

[0060] <Molecular weight of macromonomer (M)> Measurement was performed using GPC (HLC-8320 manufactured by Tosoh Corporation). A 0.2% by mass solution of tetrahydrofuran (M) was prepared, and then a column (TSK gel SuperHZM-M (inner diameter 4.6 mm, length 15 cm), HZM-M (inner diameter 4 .6mm, length 15cm), HZ-2000 (inner diameter 4.6mm, length 15cm), TSK Guard column SuperHZ-L (inner diameter 4.6 mm, length 3.5 cm) is installed. 10 μl of the above solution was injected into the device with the sorbent, and the flow rate was 0.35 ml / min., and the eluent was tetrahydrofuran. Hydrofuran (stabilizer: BHT), column temperature: 40°C, standard polystyrene Mw, Mn, and Mw / Mn were calculated by conversion.

[0061] <Molecular weight of (meth)acrylic graft copolymer (A)> The measurements were performed using GPC (HLC-8320 manufactured by Tosoh Corporation). A 0.2% by mass solution of (meth)acrylic graft copolymer (A) in tetrahydrofuran was prepared. After preparation, two columns (TSKgel Super HZM-H, 6.0 mm inner diameter, Length 15cm), TSKguardcolumn SuperHZ-H (inner diameter 4.6mm 10 μl of the above solution was injected into the device equipped with a 3.5 cm long tube (3.5 cm in length) at a flow rate of 0.5 ml / min. The measurements were performed under the following conditions: 1 min, eluent: tetrahydrofuran (stabilizer: BHT), column temperature: 40°C. The Mw, Mn, and Mw / Mn were calculated in terms of standard polystyrene.

[0062] <Friction coefficient at 40℃> The obtained (meth)acrylic graft copolymer (A), YUBASE4, was The lubricating oil composition was prepared by heating the composition to 65°C and mixing for 10 minutes. Optimol Instruments Pruftechnik GmbH The friction coefficient was measured at 40°C using a 100% polyester resin (manufactured by Epson). The measurement conditions were as follows: The coefficient of friction was evaluated 30 minutes after the start of the test. Test method: Ball-on-disc (ball diameter: 10 mm, ball and disc material Quality: SUJ2, discs were either DLC treated or untreated as described below. Each was used. The balls used were untreated. DLC treatment: DLC of ta-C synthesized by PVD method is applied to the substrate with a thickness of 0.5 μm and hardness of 4 Coated with ,000~6,000HV and Ra<0.05μm. Test mode: round trip (50Hz, stroke 1mm) Load capacity: 200N

[0063] [Production Example 1] (Synthesis of Co complex (cobalt chain transfer agent)) In a synthesis apparatus equipped with a stirrer, cobalt(II) acetate tetrahydrate ( 0.62 g (2.5 mmol) of diphenylglyoxime (Higashiyama Chemical Co., Ltd., Wako Special Grade) and EP grade (manufactured by Kyokasei Co., Ltd.) 1.30 g (5.0 mmol) and 47 ml of deoxygenated cyclopentyl methyl ether (Tokyo Chemical Industry Co., Ltd., EP grade, commercial Product name: CPME) was added and stirred at 25°C for 2 hours. Next, boron trifluoride diethyl ether complex (Tokyo Chemical Industry Co., Ltd., EP grade) 3.2 The mixture was filtered and the solid was pre-blown with nitrogen. The mixture was washed with 1.25 ml of deoxygenated CPME at 20°C under 1000 Pa. After drying for 12 hours, 1.49 g (2.2 mmol, yield 89% by mass) of brown solid Co complex was obtained. obtained.

[0064] [Production Example 2] (Synthesis of Macromonomer (M)) In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 58 parts of YUBASE4 and Acryles Alkyl SL (manufactured by Mitsubishi Chemical Corporation, product name: SLMA, an alkyl group with 12 carbon atoms) A mixture of alkyl methacrylate and alkyl methacrylate with 13 carbon atoms in the alkyl group. 98 parts of methyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: MMA), 2 parts of 0.005 parts of the Co complex prepared in Example 1 was added, the liquid temperature was raised to 40°C, and the mixture was stirred with nitrogen. The mixture was bubbled for 2 hours to remove dissolved oxygen. t-Butyl peroxy-2-ethylhexanoate (manufactured by Arkema Yoshitomi Co., Ltd., product name: Lupero Add a mixture of 0.1 parts of hexane and heat to 90°C and stir for 2.5 hours. After that, a mixture of YUBASE4 (10 parts) and Luperox 26 (0.7 parts) was added to the After the dripping, the temperature was raised to 105°C and held for 1.5 hours. Add 20 parts of the above and cool to obtain YUBASE containing 52.6% by mass of macromonomer (M). 4 solutions were obtained. The results of GPC of the obtained macromonomer (M) are shown in Table 1.

[0065] <Example 1> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 50 parts of YUBASE4 and the mixture obtained in Example 2 were added. The obtained macromonomer (M) YUBASE4 solution was mixed with 47.6 parts of n-butyl acrylate. 45 parts of acrylate (manufactured by Mitsubishi Chemical Corporation, product name: nBA), 45 parts of lauryl acrylate (Osaka Organic Chemicals 30 parts of t-butylperoxy-2-ethylhexyl ether (trade name: LA, manufactured by Kagaku Co., Ltd.) as a polymerization initiator. 0.03 parts of dihexanoate (NOF Corp., trade name: Perbutyl O) as a chain transfer agent Add 0.4 parts of α-methylstyrene dimer (NOF Corp., product name: Nofumer MSD) and stir. The dissolved oxygen was removed by bubbling nitrogen while stirring. The liquid temperature was raised to 85°C and then left for 3.5 hours. After holding, a mixture of YUBASE 4 (42 parts) and Perbutyl O (0.015 parts) After keeping the temperature at 85°C for 1 hour, YUBASE4 (30 parts) was added dropwise. A mixture of 0.5 parts of PERBUTYL O and 0.5 parts of PERBUTYL O was added dropwise over 1 hour. After heating to 100°C and holding for 1 hour, 41.1 parts of YUBASE4 was added and cooled. A YUBASE4 solution containing 35% by mass of acrylic copolymer was obtained. The evaluation results of the lubricating oil composition containing the film surface friction reducer are shown in Table 2. The polymer composition in Table 2 is the macromonomer (M) in This also includes constituent units.

[0066] <Example 2> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 50 parts of YUBASE4 and the mixture obtained in Example 2 were added. The obtained macromonomer (M) was mixed with 47.6 parts of YUBASE4 solution, 56 parts of nBA, and L Add 19 parts of A, 0.03 parts of Perbutyl O, and 0.4 parts of Nofumer MSD while stirring. Nitrogen was bubbled through the solution to remove dissolved oxygen. The liquid temperature was raised to 85°C and held for 3.5 hours. A mixture of YUBASE4 (42 parts) and Perbutyl O (0.015 parts) was added to the After holding at 85°C for 1 hour, YUBASE4 (30 parts) and Parb were added dropwise. A mixture of 0.5 parts of ethyl alcohol and 0.1 parts of ethyl alcohol was added dropwise over 1 hour. The temperature was then raised to 110°C. After holding for 1 hour, 41.1 parts of YUBASE4 was added and cooled, and the (meth)acrylic copolymer was added. A YUBASE4 solution containing 35% by mass of the polymer was obtained. The evaluation results of the lubricating oil composition containing the friction reducing agent are shown in Table 2. The friction characteristics were evaluated by DLC treatment. The disks used were

[0067] <Example 3> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 30 parts of YUBASE4 and the mixture prepared in Example 2 were added. Add 85.7 parts of the obtained YUBASE4 solution of macromonomer (M) and add nitrogen while stirring. The liquid temperature was raised to 85°C and YUBASE4 (25 parts) was added. ), nBA (55 parts), Nofumer MSD (0.9 parts), t-amyl peroxide as a polymerization initiator Oxy-2-ethylhexanoate (Arkema Yoshitomi Co., Ltd., product name: Luperox 575) A mixture of 0.1 parts was added dropwise over 4 hours. After holding at 85°C for 1 hour, A mixture of SE4 (50 parts) and Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. The temperature was raised to 110°C and held for 1 hour, after which YUBASE4 (39.9 parts) was added and cooled. The resulting solution was cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic copolymer. The evaluation results of the lubricating oil composition containing the friction reducer are shown in Table 2. The treated disks were used.

[0068] <Example 4> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 30 parts of YUBASE4 and the mixture prepared in Example 2 were added. 47.6 parts of the obtained YUBASE4 solution of macromonomer (M) was added and the mixture was heated under nitrogen while stirring. The liquid temperature was raised to 85°C and YUBASE4 (25 parts) was added. ), nBA (55 parts), LA (17 parts), acrylic acid (manufactured by Mitsubishi Chemical Corporation, trade name: AA ) (3 parts), Luperox 575 (0.1 parts), and Nofmar MSD (0.9 parts) The mixture was added dropwise over 4 hours. After keeping it at 85°C for 1 hour, YUBASE4 (50 parts) and A mixture of Luperox 575 (0.5 parts) was added dropwise over 1.5 hours. The temperature was raised to 110°C. After holding for 1 hour, YUBASE4 (58.1 parts) was added and cooled. A YUBASE4 solution containing 35% by mass of the copolymer was obtained. The evaluation results of the lubricating oil composition containing the above are shown in Table 2. The friction characteristics were evaluated using DLC-treated discs. We used the .

[0069] <Example 5> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 30 parts of YUBASE4 and the mixture prepared in Example 2 were added. 47.6 parts of the obtained YUBASE4 solution of macromonomer (M) was added and the mixture was heated under nitrogen while stirring. The liquid temperature was raised to 85°C and YUBASE4 (25 parts) was added. ), nBA (55 parts), LA (17 parts), 4-hydroxybutyl acrylate (Mitsubishi Chemical Cal Corporation, product name: 4HBA) (3 parts), Luperox 575 (0.1 parts), Nofmer M A mixture of SD (0.9 parts) was added dropwise over 4 hours. After keeping the temperature at 85°C for 1 hour, A mixture of YUBASE4 (50 parts) and Luperox 575 (0.5 parts) was applied for 1.5 hours. The temperature was raised to 110°C and held for 1 hour, after which YUBASE4 (58.1 parts) was added. The mixture was heated and cooled to obtain a YUBASE4 solution containing 35% by mass of a (meth)acrylic copolymer. The evaluation results of the lubricating oil composition containing the obtained friction reducer are shown in Table 2. A DLC-treated disk was used.

[0070] <Comparative Example 1> YUBASE4, which does not contain a (meth)acrylic copolymer, was used for the evaluation. The results are shown in Table 2. A DLC-treated disk was used for the friction property evaluation. <Comparative Example 2> In a reaction vessel equipped with a stirrer, a condenser, and a thermometer, 72.6 parts of YUBASE4 and nBA 45 parts, LA 30 parts, SLMA 25 parts, Perbutyl O 0.03 parts, Nofmer MS 0.15 parts of D was added, and dissolved oxygen was removed by bubbling nitrogen while stirring. After heating to 3.5°C and holding for 3.5 hours, YUBASE4 (42 parts) and Perbutyl O (0.0 15 parts) was added dropwise over 2 hours. After keeping the temperature at 85°C for 1 hour, YUBASE4 (60 parts) and 1,1,3,3-tetramethylbutylperoxy-2-ethyl A mixture of 1 part of hexanoate (manufactured by NOF Corp., trade name: Perocta O) (0.5 parts) was added to 1 After that, the temperature was raised to 110°C and held for 1 hour, and then YUBASE4 was added dropwise to the Add 1.1 parts of YUBAS containing 35% by mass of (meth)acrylic copolymer and cool. The lubricating oil composition containing the friction reducer thus obtained was evaluated and the results are shown in Table 2. Friction A DLC-treated disk was used for the characteristic evaluation.

[0071] <Comparative Example 3> Add 30 parts of YUBASE4 to a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and stir. The dissolved oxygen was removed by bubbling nitrogen into the solution. The liquid temperature was raised to 85°C. (25 parts), n-butyl methacrylate (manufactured by Mitsubishi Chemical Corporation, trade name: BMA) (45 parts ), lauryl methacrylate (Mitsubishi Chemical Corporation, trade name: LMA) (30 parts), SLM A (25 parts), Luperox 575 (0.1 parts), Nofmar MSD (0.4 parts) The mixture was added dropwise over 4 hours. After holding at 85°C for 1 hour, YUBASE4 (50 parts) was added. A mixture of 0.5 parts of Luperox 575 was added dropwise over 1.5 hours. The temperature was raised to 110°C. After heating and holding for 1 hour, YUBASE4 (80.6 parts) was added and cooled. A YUBASE4 solution containing 35% by mass of a acrylic copolymer was obtained. The evaluation results of the lubricating oil composition containing the compound are shown in Table 2. The friction characteristics were evaluated using DLC-treated diamond. A sque was used.

[0072] <Comparative Example 4> The evaluation results of the lubricating oil composition containing the friction reducer obtained in Example 2 are shown in Table 2. For the evaluation of friction characteristics, a disk that was not subjected to DLC treatment was used.

[0073] Comparative Example 1 does not contain the (meth)acrylic graft copolymer (A), and therefore has a high friction coefficient. In addition, in Comparative Example 2 and Comparative Example 3, the (meth)acrylic graft copolymer of the present invention was used. The coefficient of friction was high because a (meth)acrylic copolymer other than the compound (A) was used. In Example 4, no hard carbon thin film was formed on the surface of any of the structural components, so the friction coefficient The numbers got higher.

[0074] [Table 1]

[0075] [Table 2]

[0076] The abbreviations in Tables 1 and 2 are as follows. SLMA: Alkyl methacrylate with 12 carbon atoms in the alkyl group and A mixture of alkyl methacrylates with 13 carbon atoms (manufactured by Mitsubishi Chemical Corporation, product name: Acrylate) Riester SL) MMA: Methyl methacrylate (Mitsubishi Chemical Corporation, product name: Acryester M) LMA: Lauryl methacrylate (Mitsubishi Chemical Corporation, product name: Acryester L) LA: Lauryl acrylate (Osaka Organic Chemical Industry Co., Ltd., product name: LA) BMA: Butyl methacrylate (Mitsubishi Chemical Corporation, product name: Acryester B) nBA: n-Butyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name: butyl acrylate) AA: Acrylic acid (manufactured by Mitsubishi Chemical Corporation, product name: acrylic acid) 4HBA: 4-Hydroxybutyl acrylate (manufactured by Mitsubishi Chemical Corporation, product name: 4HBA )

Claims

1. It has a main chain polymer structure and a side chain polymer structure, and the alkyl group has 11 to 30 carbon atoms. (Meth)acrylate (a)-derived structural unit is contained in the side chain polymer structure A friction reducing agent for a hard carbon thin film surface, comprising an acrylic graft copolymer (A).

2. The main chain polymer structure is an alkyl(meth)acrylate having an alkyl group of 1 to 10 carbon atoms.

2. The friction reducing agent for a hard carbon thin film surface according to claim 1, comprising a structural unit derived from (b).

3. The (meth)acrylic graft copolymer (A) is further represented by the following general formula (1): The hard carbon thin film according to claim 1, further comprising a structural unit derived from a (meth)acrylate (c). Surface friction reducer. 【Chemistry 1】 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 contains a hydrogen atom or a polar group represents an organic group.)

4. The polar group of the (meth)acrylate (c) is a hydroxyl group or a carboxyl group. The friction reducing agent for hard carbon thin film surfaces according to claim 3.

5. The (meth)acrylic graft copolymer (A) is a vinyl radical polymerizable monomer ( The polymer according to claim 1, comprising a structural unit derived from m1) and a structural unit derived from a macromonomer (M). Friction reducer for hard carbon thin film surfaces.

6. The hard carbon according to claim 5, wherein the macromonomer (M) has a structure represented by the following formula (2): Friction reducer for thin film surfaces. 【Chemistry 2】 (In the formula, X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CH 2 Show OH S, Y 1 ~Y n are each independently a monomer constitutional unit of the macromonomer (M), X bonded to a vinyl group of a certain vinyl radical polymerizable monomer (m2) 1 ~X n-1 Other than Z represents a terminal group, and n represents an integer of 2 to 10,000.

7. A lubricating oil composition comprising the friction reducing agent for hard carbon thin film surfaces according to any one of claims 1 to 6. Composition.

8. It has a main chain polymer structure and a side chain polymer structure, and the alkyl group has 11 to 30 carbon atoms. (Meth)acrylate (a)-derived structural unit is contained in the side chain polymer structure A friction reducer comprising an acrylic graft copolymer (A), and a plurality of parts, At least one of the components of the structural member has a hard carbon thin film on a surface thereof.

9. The structural member according to claim 8 , wherein the hard carbon thin film is a DLC thin film.

10. The main chain polymer structure is an alkyl(meth)acrylate having an alkyl group of 1 to 10 carbon atoms. The structural member according to claim 8, comprising a constitutional unit derived from (b).

11. The (meth)acrylic graft copolymer (A) is further represented by the following general formula (1):

9. The structural member according to claim 8, comprising a constitutional unit derived from a (meth)acrylate (c). 【Chemistry 3】 (In the formula, R 1 is a hydrogen atom or a methyl group, R 2 contains a hydrogen atom or a polar group represents an organic group.)

12. The polar group of the (meth)acrylate (c) is a hydroxyl group or a carboxyl group.

12. The structural member of claim 11.

13. The (meth)acrylic graft copolymer (A) is a vinyl radical polymerizable monomer ( The polymer according to claim 8, comprising a structural unit derived from m1) and a structural unit derived from a macromonomer (M). Structural components.

14. The macromonomer (M) has a structure of the following formula (2): Parts. 【Chemistry 4】 (In the formula, X 1 ~X n-1 are each independently a hydrogen atom, a methyl group, or CH 2 Show OH S, Y 1 ~Y n are each independently a monomer constitutional unit of the macromonomer (M), X bonded to a vinyl group of a certain vinyl radical polymerizable monomer (m2) 1 ~X n-1 Other than Z represents a terminal group, and n represents an integer of 2 to 10,000.

Citation Information

Patent Citations

  • Low friction slide member

    JP2006306938A

  • A polymer that improves friction on surfaces coated with diamond-like carbon.

    JP2014516097A